2002
DOI: 10.2298/jsc0206457s
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the kinetics of extraction of resinoids and hypericines from the amber, Hypericum perforatum L

Abstract: The kinetics of the extraction of the overall extracted materials (resinoids), total hypericine, hypericine and pseudohypericine from amber (Hypericum perforatum L) was investigated by the procedure of maceration both with and without ultra-sound, using methanol as the extractant. It was found that the period of fast extraction with intensification of the extraction of resinoid by ultra-sound was significantly shorter (about 20 minutes) than was needed for the extraction without ultra-sound (about 5 h). Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Several mathematical models (empirical or physical models) have been employed to describe the kinetics of TH extraction from H. perforatum : a kinetic model of the first‐order reaction, 19 unsteady‐state diffusion model, 11 film theory model, 14 parabolic diffusion model and Elovich's equation 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mathematical models (empirical or physical models) have been employed to describe the kinetics of TH extraction from H. perforatum : a kinetic model of the first‐order reaction, 19 unsteady‐state diffusion model, 11 film theory model, 14 parabolic diffusion model and Elovich's equation 14 …”
Section: Methodsmentioning
confidence: 99%
“…Extraction of total hypericin (TH) which relates to the extraction of the group of compounds (hypericin, pseudohypericin and their biosynthetic precursors) from H. perforatum dried material has been the main objective of a large number of studies in the literature 11–18 . Šmelcerović et al 11 investigated the extraction of hypericin and pseudohypericin from amber of H. perforatum plant by maceration and ultrasound‐assisted extraction (UAE) using ethanol as solvent.…”
Section: Introductionmentioning
confidence: 99%
“…While CCS gave the best recovery of pseudohypericin (87%), the Sephadex procedure yielded a higher recovery of hypericin than CCS (91 vs 76%). 134 Five triterpene saponins were isolated from Gypsophila paniculata with an HBuMWat(0.02% TFA) SS. A comparison between the 300 mL CCS instrument and 20 × 250 mm C 18 HPLC reported that CCS had larger sample loading (220 vs 30 mg), longer separation times, shorter preprocessing times, better reproducibility, and lower cost.…”
Section: Workflowmentioning
confidence: 99%
“…[6±8] and the most significant compounds (hypericine and pseudohypericine) [6] gained by the maceration procedure. The process of H. perforatum L. extraction was significantly activated by the application of ultra-sound [6].…”
Section: Introductionmentioning
confidence: 99%
“…The process of H. perforatum L. extraction was significantly activated by the application of ultra-sound [6]. There is little information about the extraction of H. perforatum L. using a high pressure extraction method [9].…”
Section: Introductionmentioning
confidence: 99%